If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(1 + -6a) = 24a + -22 (1 * -4 + -6a * -4) = 24a + -22 (-4 + 24a) = 24a + -22 Reorder the terms: -4 + 24a = -22 + 24a Add '-24a' to each side of the equation. -4 + 24a + -24a = -22 + 24a + -24a Combine like terms: 24a + -24a = 0 -4 + 0 = -22 + 24a + -24a -4 = -22 + 24a + -24a Combine like terms: 24a + -24a = 0 -4 = -22 + 0 -4 = -22 Solving -4 = -22 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 7(x+3)=7(x+9) | | 5+3(a+4)=2(a+1) | | -.125x=-5 | | 2(3x+5)=16x | | 8x+72+6x=19(s) | | 16-6x=-14-9x | | F(10)=7.5x | | 8x^2-2=-23 | | 14x+15y= | | Px+ax=r | | 3(y-5)=27 | | -15y=75 | | x+10=x+20 | | 6x^2=-7x+3 | | F(0)=7.5x | | 6-5n+7= | | 40-5x=30 | | 9+(-4)=x | | 2x^2-30x=3500 | | t^2-10t+12.5=0 | | 4x-2xy+x-3+xy= | | 0.36(2x-5)-0.76(3x+2)+0.83=30.27 | | h=60t-5t | | 3/3b+4=2/b-4 | | 6a=8-9+6a | | 11+(-6)(3)=x | | 4.5(3x-2)=9(x+4) | | -39-3x=-4x+2(5x-6) | | 2+6x=8x+0 | | x^4-4x^3+4x^2-7x+8=0 | | 8(2.85)+-2=3(2.85)+12.25 | | 8+60+x+51=180 |